2015
DOI: 10.1515/crelle-2014-0147
|View full text |Cite
|
Sign up to set email alerts
|

Volume of minimal hypersurfaces in manifolds with nonnegative Ricci curvature

Abstract: Abstract. We establish a min-max estimate on the volume width of a closed Riemannian manifold with nonnegative Ricci curvature. More precisely, we show that every closed Riemannian manifold with nonnegative Ricci curvature admits a PL Morse function whose level set volume is bounded in terms of the volume of the manifold. As a consequence of this sweep-out estimate, there exists an embedded, closed (possibly singular) minimal hypersurface whose volume is bounded in terms of the volume of the manifold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The precise statement of their result is actually rather explicit about the geometric dependence of the constant they obtain, see Theorems 5.1 therein; in particular, their estimate implies that all unit volume positive Ricci curvature metrics have their Almgren-Pitts widths uniformly bounded from above as well. The latter bound was also proven by Sabourau [38]. We remark that the Almgren-Pitts width of a three-sphere with positive Ricci curvature is precisely the least possible area of an embedded minimal surface (see [43], Theorem 15), while the Simon-Smith width of such three-sphere is equal to the least possible area of an embedded minimal two-sphere (see [24], proof of Theorem 3.4).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The precise statement of their result is actually rather explicit about the geometric dependence of the constant they obtain, see Theorems 5.1 therein; in particular, their estimate implies that all unit volume positive Ricci curvature metrics have their Almgren-Pitts widths uniformly bounded from above as well. The latter bound was also proven by Sabourau [38]. We remark that the Almgren-Pitts width of a three-sphere with positive Ricci curvature is precisely the least possible area of an embedded minimal surface (see [43], Theorem 15), while the Simon-Smith width of such three-sphere is equal to the least possible area of an embedded minimal two-sphere (see [24], proof of Theorem 3.4).…”
Section: Introductionmentioning
confidence: 60%
“…Considering examples of Riemannian metrics constructed by Burago and Ivanov [11], Guth showed that there are unit volume metrics on S 3 with arbitrarily large Almgren-Pitts width (see [20], Appendix A, and also [38], Section 7, for further results in this direction). Thus, no upper bound for the normalised width can be valid for all Riemannian metrics on S 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we consider two different notions of sweepout and waist similar but somewhat different to those introduced by Gromov in [11, §6]; see Definitions 1.1 and 1.10. With these notions, universal upper bounds on the waist of one-parameter families of one-cycles sweeping out essential surfaces of closed Riemannian manifolds were obtained in [24]. Our first theorem extends this result to the waist of multi-parameters families of one-cycles sweeping out any closed Riemannian manifold.…”
Section: Introductionmentioning
confidence: 75%
“…However, such a construction is not always possible in general. A different path was taken in [24], where a retraction from a different filling Q was constructed by considering all the simplices lying in the 2-skeleton of Q at the same time (and not only one at a time) and by proceeding by induction on the dimension of the higher-dimensional skeleta of Q from there, using a topological assumption on the manifold. In the proof of Theorem 1.3, where the manifold M is arbitrary, we take yet a different approach.…”
Section: Introductionmentioning
confidence: 99%
“…Remark 1.9. In [33] Stephane Sabourau independently obtained upper bounds on the width and volume of the smallest minimal hypersurface on Riemannian manifolds with Ricci ≥ 0.…”
Section: Previous Workmentioning
confidence: 99%